Analisis Implementasi Sistem Aplikasi Signal Polri Pada Kepatuhan Wajib Pajak Kendaraan Bermotor di Jakarta Pusat - Dewi, Dina Anisia; Pebyanti, Amartya; Putri, Nurul Amalia; Rahmi, Notika (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
August 2021 korlantas began to introduce the Samsat Digital Nasional (Signal) application to the Public. But because this application is operated digitally, there are still many taxpayers, especially parents who cannot easily use or take advantage of it, so there are still many who prefer to manually extend the motor vehicle tax directly to Samsat. If that continues to happen, it will cause a potential queue that is quite long and long. This research aims to analyze the Signal Polri Application system on the compliance of Motor Vehicle taxpayers in Central Jakarta. The method used is a qualitative method with data collection, interview, observation, and documentation techniques. The research was conducted at the Central Jakarta Samsat Office. The results of his research show that the policy implementation process is to build a network so that public policy goals can be realized as a result of government activities. Can be interpreted as a strategy to achieve the policy goals that have been set. The success and failure of the policy implementation process can be assessed in terms of the implementation of the program made. Policy implementation is also influenced by who is appointed and authorized to carry out the program, especially as an implementer. The results of this study show that the user presentation of the Signal Polri Application Program is only 1.50% - 3.84% during the last 3 years from the total number of motor vehicle users in Central Jakarta. The lack of numbers is caused by the lack of knowledge from taxpayers towards the Signal Polri Application Program because the socialization carried out by the samsat to taxpayers has not been too extensive.